Model Sistem Pendukung Keputusan Penilaian Prestasi Marketing Agent Menggunakan Metode Analitycal Hierarchy Process (AHP) - Yopi Handrianto; Ghofar Taufiq; Santiyana Yulia (Universitas Pradita, 2021)
Abstract: PT WOM Finance tbk is a private financial corporation located in Central Jakarta which always strives to continuously improve internal and external quality in order to compete with other companies. One effort that needs to be done is to conduct an assessment of the performance of an external employee called Marekting Agent. However, the assessment conducted on PT WOM Finance tbk not yet the existence of a system that resulted in assessment, this is what makes the need for a system capable of managing performance appraisal data marketing agent and generate rankings from the calculation of the value of Marketing Agent (MA). Thus, to be more accurate in the assessment of marketing agents, companies sebaikanya selective assessment of marketing agents. The method used in decision support system one of them is Analytical Hierarchy Process (AHP) which can be used in problem solving which is subjective and can also be used to solve the problem in the achievement of marketing agent achievement. With the final result obtained by using Analytical Hierarchy Process (AHP) method is to know Marketing Agent at PT WOM Finance tbk, with the most superior criterion is candidate Ari Darmawan with 52,27% percentage.